2018
DOI: 10.1371/journal.pone.0193598
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing activation of overlying axons with epiretinal stimulation: The role of fiber orientation and electrode configuration

Abstract: Currently, a challenge in electrical stimulation of the retina with a visual prosthesis (bionic eye) is to excite only the cells lying directly under the electrode in the ganglion cell layer, while avoiding excitation of axon bundles that pass over the surface of the retina in the nerve fiber layer. Stimulation of overlying axons results in irregular visual percepts, limiting perceptual efficacy. This research explores how differences in fiber orientation between the nerve fiber layer and ganglion cell layer l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 62 publications
5
35
0
Order By: Relevance
“…Model fits to behavioral data suggest that sensitivity to electrical stimulation is not confined to the axon initial segment (38), but can be modeled as falling off with different decay constants along the axon (with ranging from 500-1,420 μm) and orthogonally from the axon (with ranging from 86-437 μm), resulting in visual percepts ranging from 'blobs' to 'streaks' and 'wedges' depending on both the relative values of and , and the retinal location of the stimulating electrode. These results are in agreement with theoretical work suggesting an anisotropic spread of current in the retinal tissue (29) as well as previous animal literature demonstrating that epiretinal stimulation leads to activation of passing axon fibers (18,38,39,41), which can severely distort the quality of the generated visual experience (16,18,40,42,43). Our findings suggest that the spatial distortions reported by patients are not arbitrary, but rather depend on the topographic organization of optic nerve fiber bundles in each subject's retina, which can be captured by a computational model.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Model fits to behavioral data suggest that sensitivity to electrical stimulation is not confined to the axon initial segment (38), but can be modeled as falling off with different decay constants along the axon (with ranging from 500-1,420 μm) and orthogonally from the axon (with ranging from 86-437 μm), resulting in visual percepts ranging from 'blobs' to 'streaks' and 'wedges' depending on both the relative values of and , and the retinal location of the stimulating electrode. These results are in agreement with theoretical work suggesting an anisotropic spread of current in the retinal tissue (29) as well as previous animal literature demonstrating that epiretinal stimulation leads to activation of passing axon fibers (18,38,39,41), which can severely distort the quality of the generated visual experience (16,18,40,42,43). Our findings suggest that the spatial distortions reported by patients are not arbitrary, but rather depend on the topographic organization of optic nerve fiber bundles in each subject's retina, which can be captured by a computational model.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the variability in phosphene shape, all subjects reported seeing elongated phosphenes on at least a subset of electrodes (Figure 3C). Although the electric field generated by a disk electrode is radially symmetric, the neural tissue induces anisotropies in the electric field, and stimulation of axon fibers produces even more striking anisotropies in patterns of neural activation within the retina (29). It has long been known that external stimulation of an axon induces an action potential that travels both backward to the cell body and forward to the synaptic terminals (63,64).…”
Section: Phosphene Shape Is Mediated By Axonal Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…For both epi-retinal and sub-retinal stimulation, ultrashort pulses (shorter than 0.15 ms in Chang et al, 2019, and shorter than 0.1 ms in Tong et al, 2019a) were demonstrated to be effective at avoiding axon bundle stimulation. Esler et al (2018a) proposed to simultaneously stimulate multiple electrodes aligned with the axon bundles to minimize the bundle activation. The proposal was based on the fact that the excitable parts of RGC are the AIS.…”
Section: Spatial Resolutionmentioning
confidence: 99%
“…However, a major challenge with current retinal prostheses is the inability to achieve focal tissue activation. Because epiretinal prostheses sit on top of the optic fiber layer, these devices may accidentally stimulate passing axon fibers, which could antidromically activate cell bodies located peripheral to the point of stimulation [3]- [5]. This can cause nontrivial perceptual distortions [6]- [8] that may severely limit the quality of the generated visual experience [9], [10].…”
Section: Introductionmentioning
confidence: 99%